Dissociative and Hallucination as Main Symptoms of Borderline Personality Disorders: A Case report - Yusmadewi, Aaliyah; Fatwa, Ahmad Misbahul Ulum; Makka, Isna Meirilla Zahara Al; Billah, Illa; Imron, Muhammad Istio Hadi Al; Suwarti, Ariyani Sri; Algristian, Hafid (Indonesian Scientific Publication, 2025)
Borderline Personality Disorder (BPD) is a complex psychiatric condition often accompanied by dissociative symptoms and hallucinations. These symptoms are not merely comorbid features but appear to be integral aspects of the disorder's pathology. This case report presents a 20-year-old female patient with a history of childhood trauma and persistent emotional distress, who exhibited dissociation and auditory hallucinations as primary clinical features. Approximately 75–80% of individuals with BPD experience dissociation, while 30–50% report hallucinations, particularly under emotional stress. In this case, dissociative states such as depersonalization and amnesia preceded hallucinatory experiences, suggesting a causal link. The patient demonstrated episodes of memory loss, out-of-conscious behavior, and auditory command hallucinations, which significantly impaired her functioning. These symptoms were exacerbated by academic pressure and unresolved trauma. The interplay between dissociation and hallucination highlights the importance of trauma-informed, emotion-regulation-focused interventions. Clinicians should assess these symptoms systematically, as their presence may indicate a more severe clinical profile and the need for integrative therapeutic strategies.